EFFECTIVENESS OF TRAPEZOIDAL AND SINUSOIDAL SUBMERGEDWAVE BREAKERS IN REDUCING WAVE AMPLITUDE - Fadhel Atras, Muh
Submerged breakwater is one of breakwater type that is commonly used as a coast protector from wave hit. Various forms of submerged breakwaters have been developed such as trapezoidal and sinusoidal shapes. In this final project, the effectiveness of submerged breakwaters with these forms will be discussed through mathematical modeling and numerical simulation. The effectiveness of submerged breakwaters can be seen from the transmission coefficient (Kt), which is the ratio of the amplitude of the wave that has passed through the breakwater (transmission amplitude) to the amplitude of the wave coming from the sea (amplitude comes). Shallow water equation will be used as main model in this final project. The equation will be solved analytically to get the transmission coefficient of each submerged breakwater form. We solve the model numerically using the finite volume method on staggered grid. Furthermore, wave propagation phenomena will be assessed when the dimensions of submerged breakwaters with certain forms are varied. From the validation of numerical simulation with analytical solution, we got that the Kt error is small enough. For the trapezoidal submerged breakwaters, the most effective form of reducing wave amplitude is when the sloping side is increasingly steep towards upright. In general, the value of Kt from sinusoidal wave breakers is smaller than other forms because it allows resonance Bragg, which is resonance which causes large reflection waves. This resonance occurs when the incoming wavelength is twice that of the wavelength of the submerged breakwater. The numerical simulation results are then validated with physical experiment data, and it is found that the Kt value error is quite small. This means that the numerical simulation performed can describe the wave propagation phenomenon well.